On the congruence of exchange rates under a system of bilateral trade. A reply - C. BRESCIANI-TURRONI (PSL Quarterly Review, 2014)
A reply to Dr. Gioacchino d’Ippolito’s article on the problem of the concordance of direct exchange rates and cross-rates under a system of bilateral trade.